JUEGOS DE PALABRAS EN RUIZ DE MOROS - Ballester, Xaverio (Myrtia, 2001)
Classical Latin literature had a long tradition of puns, mainly due to the fact that Latin language showed great predisposition towards puns. The Romans themselves were very fond of them, indeed. Likewise, puns stand out as a very important feature in the Latin poetry of Ruiz de Moros, a Renaissance Spanish author, who would make jokes playing with the sounds and meanings of vernacular words as well. There are so many and so different puns in the Ruiz de Moros poetry that one could feel inclined to make a generalization or a typological study of this funny kind of literary "ornatus".